2014
DOI: 10.1007/s11105-014-0779-0
|View full text |Cite|
|
Sign up to set email alerts
|

Loss of Function of the Carotenoid Isomerase Gene BrCRTISO Confers Orange Color to the Inner Leaves of Chinese Cabbage (Brassica rapa L. ssp. pekinensis)

Abstract: Chinese cabbage varieties with orange inner leaves are of interest due to their attractive appearance and high carotenoid content. Previously, a recessive locus, Br-or, that confers this trait was mapped to linkage group A09 in Brassica rapa, and Bra031539 was identified as the candidate gene. We used a backcross population consisting of 1,392 individuals for fine mapping; three linked markers delimited the Br-or locus to a region of 9.47 kb, which contained only one predicted functional gene, Bra031539 (the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 28 publications
1
53
3
Order By: Relevance
“…This result is inconsistent with some previous studies which show that the mRNA level of a Br-or candidate gene (Bra031539) is lower in the orange inner leaves than in the white inner leaves [10, 15]. To understand the difference, the promoter sequence of Bra031539 was analyzed.…”
Section: Resultscontrasting
confidence: 83%
“…This result is inconsistent with some previous studies which show that the mRNA level of a Br-or candidate gene (Bra031539) is lower in the orange inner leaves than in the white inner leaves [10, 15]. To understand the difference, the promoter sequence of Bra031539 was analyzed.…”
Section: Resultscontrasting
confidence: 83%
“…A BAC library was developed to clone BrCRTISO in the orange head material. A 90-bp DNA deletion in the promoter and a 501-bp DNA insertion prior to the stop codon are the distinctive features revealed between the two experimental materials (Su et al, 2014). Li et al (2015) found that an orange-type A21530 mutant also lacks the 3' end sequence.…”
Section: Discussionmentioning
confidence: 92%
“…Using an F2S4 population, a single recessive gene, Br-or, was previously localized to a 16.7-kb region, with three ORFs (open reading frames) predicted in the target area (Zhang et al, 2013). Br-or was then localized to a 9.47 kb region containing one predicted gene (Su et al, 2014). Using two insertion-deletion (InDel) markers, SB14001 and SB13049, the target gene was subsequently localized to a 65.555 kb region containing 17 candidate genes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported the identification of a CRTISO as the candidate gene for orange head by high-resolution genetic mapping using F2S4 population [15]. Loss of BrCRTISO function, upregulation of the upstream genes, and downregulation of downstream genes lead to the accumulation of prolycopene and confer an orange color to the inner head leaves in Chinese cabbage [16]. Previous studies have shown that the CRTISO protein is relatively conserved in plants.…”
Section: Resultsmentioning
confidence: 99%